ANALISIS BIBLIOMETRIK : TERHADAP MEDIA PEMBELAJARAN PADA SEKOLAH DASAR TAHUN 2021-2025 - Fatma Wati; Hidayah, Nurul; Ayu Reza Ningrum (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Learning media is an important part of the learning process in elementary schools that use various learning styles and different student abilities. The purpose of this study is to examine the development of research on learning media in elementary schools with a bibliometric analysis method approach using the VOSViewer application. Data from Google Scholar indexed journals were collected through the Publish or Perish application and then compiled/refined in the Mendeley application. Keyword searches in the title and abstract of the study resulted in 315 relevant articles. Published in the last 5 years, namely in 2021-2025. The results of the analysis show that the number of articles on research on Learning Media in Elementary Schools has decreased and is unstable every year. In 2021-2022, it focused on developing media in certain classes and on certain learning media, the trend is to focus on developing online learning media. Then, in 2023-2025, research on learning media in elementary schools focused on understanding concepts, learning outcomes, digital media such as wordwalls, interactive videos, Canva animations, Google cites, puzzles, audio-visual media, digital marketing, e-flashcards, e-comics, especially in the current Merdeka curriculum.